P2Y2-P2X7 receptors cross-talk in primed mesenteric endothelial cells upregulates NF-κB signaling favoring mononuclear cell adhesion in schistosomiasis - Oliveira, Nathália Ferreira; Monteiro, Matheus Macedo L. V.; Mainieri, Nathália Santos; Tamura, Augusto Shuiti; Pereira, Letícia Massimo; Crepaldi, Leticia Diniz; Coutinho-Silva, Robson; Savio, Luiz Eduardo Baggio; Silva, Claudia Lucia Martins (Frontiers in Immunology, 2024)
Schistosomiasis is an intravascular infectious disease that impacts over 200 million people globally. In its chronic stage, it leads to mesenteric inflammation with significant involvement of monocytes/macrophages. Endothelial cells lining the vessel lumens play a crucial role, and mount of evidence links this disease to a downregulation of endoprotective cell signaling favoring a primed and pro-inflammatory endothelial cell phenotype, and therefore the loss of immunovascular homeostasis.One hallmark of infectious and inflammatory conditions is the release of nucleotides to the extracellular milieu, which, in turn, act as innate messengers, activating purinergic receptors and triggering cell-tocell communication. ATP influences the progression of various diseases through P2X and P2Y purinergic receptor subtypes. Among these receptors, P2Y2 (P2Y2R) and P2X7 (P2X7R) receptors stand out, known for their roles in inflammation. However, their specific role in schistosomiasis has remained largely unexplored. Therefore, we hypothesized that endothelial P2Y2R and P2X7R could contribute to monocyte adhesion to mesenteric endothelial cells in schistosomiasis. Using a pre-clinical murine model of schistosomiasis associated to endothelial dysfunction and age-matched control mice, we showed that endothelial P2Y2R and P2X7R activation increased monocyte adhesion to cultured primary endothelial cells in both groups. However, a distinct upregulation of endothelial P2Y2R-driven canonical Ca 2+ signaling was observed in the infected group, amplifying adhesion. In the control group, the co-activation of endothelial P2Y2R and P2X7R did not alter the maximal monocyte adhesion induced by each receptor individually. However, in the infected group, this co-activation induced a distinct upregulation of P2Y2R-P2X7R-driven canonical signaling, IL-1β release and VCAM-1 expression, with underlying mechanisms involving inflammasome and NF-B signaling. Therefore, current data suggest that schistosomiasis alters endothelial cell P2Y2R/P2X7R signaling during inflammation. These discoveries advance our understanding of schistosomiasis. This intricate interplay, driven by PAMP-triggered endothelial P2Y2R/P2X7R cross-talk emerges as a potential key player in the mesenteric inflammation during schistosomiasis.